(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Discrimination is the act of favoring one group of people over another. When judging or treating someone based on their demographic traits, such as gender, age, education, employment, marital status, language spoken, and others, it is commonly associated with bias and unfairness. In today’s workplaces, discrimination is a sin. In essence, employers have a duty to offer equal employment chances to workers of different genders, colors, ethnicities, and religions, among other personal characteristics. The focus of the entire essay is on workplace discrimination and how it affects worker productivity. There is no doubt that prejudice demotivates workers and lowers potential job satisfaction (Denissen & Saguy, 2018). The study came up with the results in terms of demographic profile: female employees have the highest responses and have an age range of 25 and below. The researchers distributed the questionnaires equally to 10 male and female employees, and most of the respondents were still single on the assessment of the factors of workplace discrimination that affect the employees’ performance/productivity in terms of hiring practices, salary gap, and promotion. These variables had the same verbal interpretation of “strongly agree.” There is no significant difference between the two groups of respondents as to cited variables. Since the t-computed value is less than the t-critical value, therefore the null hypothesis of non-significance is accepted. Based on the findings, the researchers conclude that the majority of the selected respondents consider the workplace discrimination that affects the employee’s performance/productivity. Most of the respondents have encountered or experienced workplace discrimination in terms of hiring practices, salary gaps, and promotions. The researcher recommends to the Organization or Company that they should practice to eliminate workplace discrimination.